Taxes, expenditures, and the economic base : case study of New York City - Bahl, Roy W.; Campbell, Alan K.; Greytak, David (New York : London : Praeger, 1974)
There were significant changes in the population composition of New York City over the 1960-70 decade. Since a basic theme of this research is that such compositional changes are ultimately translated into tax revenue and expenditure demand effects, they have important implications for an evaluation of the longer-term fiscal health of the city government. This text emphasizes on those quantifiable facets of economic, demographic, and social change that have a particular relevance to the city fisc.
"Published in cooperation with the Maxwell School of Citizenship and Public Affairs, Syracuse University."
Includes bibliographical references and index.
ne 22/01/2019
Loans
Keywords: Taxation; New York